Potensi Tsunami Akibat Aktivitas Gunung Iliwerung dan Kesiapsiagaan Masyarakat - Nurokhim, Arif; Manessa, Masita Dwi Mandini; Gunawan, Indra (Bumi Lestari; Vol 25 No 2 (2025), 2025)
This research uses a landslide model as a potential tsunami source to map the risk impact of activities at the Iliwerung volcano. The model is assumed to consist of a single block of material that experiences a sudden and rapid landslide, directed toward the southeast of Iliwerung volcano. Using the TUNAMI (2019) code, the tsunami propagation was modeled and recorded, and the wave travel time from the source to the shore. The modeling results indicate that the tsunami could sweep across the entire southern region of Lembata Island within approximately 2-5 minutes, while the tsunami waves would reach the northern coast of Timor Island in about 8-10 minutes. This indicates that the time available for evacuation is extremely short, necessitating that the community be well-prepared to confront the potential tsunami threat. It is essential to have collaborative initiatives across different sectors, such as infrastructure, technology, and social community aspects. Institutions and communities play a crucial role in raising public awareness of the potential tsunami hazards, while the community must continuously enhance their knowledge and skills for self-evacuation.